FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEBIJAKAN DIVIDEN - Novia Ayu Puspitasari; Darsono Darsono (Diponegoro Journal of Accounting, 2014)
The Objective of this research is to analyse the influence of free cash flow, collateral assets, debt to equity ratio and profitability toward dividend policy in manufacture companies that is listed in BEI over period 2009-2011. Sampling technique used here is purposive sampling. The data is obtained based on Indonesian Capital Market Directory and audited financial reports. It is gained sample amount of 188 observations. Data analysis used descriptive statistics, classical asumption test, and multiple liniar regression analysis.  From the analysis result, it indicates that debt to equity ratio and profitability variable partially significant toward dividend policy on the level of significance less than 1 percent, while it indicates that free cash flow and collateral assets variable partially not significant toward dividend policy. While simultaneously free cash flow, collateral assets, debt to equity ratio and profitability proof significantly influent dividend policy in level less than 1 percent. Predictable of four variables toward dividend policy  is 20,4 percent as indicated by adjusted R square that is 20,4percent while the rest 79,6 percent is affected by other factors which are not included into the study model.